2021
DOI: 10.1111/jfpp.15478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xanthan gum, guar gum, and pectin on physicochemical, color, textural, sensory, and drying characteristics of kiwi fruit leather

Abstract: The present investigation was carried with the objective of developing kiwi fruit leather using different hydrocolloids. Hydrocolloids like xanthan gum (XG), guar gum (GG), and pectin (P) in three different concentrations, that is, 0.2%, 0.5%, and 1% were blended with kiwi pulp and were dried at 60°C for around 7 hr. The developed kiwi fruit leathers were analyzed for physicochemical, color, textural and organoleptic properties. The leather samples prepared with 0.5% XG, 0.5% GG, and 0.5% P showed the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
2
5
0
2
Order By: Relevance
“…Fruit leather containing 3% kappa-carrageenan and 3% gum Arabic exhibited no significant difference in DPPH activity. This is consistent with research on kiwi fruit leather made with xanthan gum, guar gum, and pectin (Barman et al, 2021 ). Therefore, the addition of 3% gum Arabic resulted in a negligible increase in comparison to the addition of 3% kappa-carrageenan.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Fruit leather containing 3% kappa-carrageenan and 3% gum Arabic exhibited no significant difference in DPPH activity. This is consistent with research on kiwi fruit leather made with xanthan gum, guar gum, and pectin (Barman et al, 2021 ). Therefore, the addition of 3% gum Arabic resulted in a negligible increase in comparison to the addition of 3% kappa-carrageenan.…”
Section: Resultssupporting
confidence: 92%
“…The antioxidant capacity of DPPH was determined to be between 47.91 and 57.18 percent in this study. These percentages were lower than those found in persimmon fruit leather, which ranged from 83.53 to 87.08% (Mohamed et al, 2018 ) and lower than those found in kiwi fruit leather, which ranged from 81.21 to 88.37% (Barman et al, 2021 ). Banana has a low antioxidant capacity (Shian & Abdullah, 2012 ).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…For each fresh and dried sample, color measurements were read 10 times. The equations that were used for the color change, whitening index, and browning index calculated in relation to L, a, and b values were as follows (Barman et al, 2021;Chouaibi et al, 2021;Cuccurullo et al, 2018).…”
Section: Color Parameters Whitening and Browning Indexesmentioning
confidence: 99%
“…Untuk mendapatkan produk yang sesuai maka dalam proses pembuatan fruit leather buah jambu air ini perlu adanya penambahan bahan tambahan pangan yang berfungsi untuk memberikan efek tekstur yang plastis dan kenyal seperti hidrokoloid. Hidrokoloid adalah kelompok heterogen polimer rantai panjang (polisakarida dan protein) yang dicirikan oleh sifat pembentukannya disperse kental dan atau gel ketika terdispersi dalam air dan banyak digunakan dalam formulasi makanan untuk meningkatkan kualitas atribut (Barman et al, 2021;Patil et al, 2017) Hidrokoloid yang sudah digunakan dalam pembuatan fruit leather adalah CMC (Carboxyl Methyl Cellulose), gum arab, agar-agar, karaginan, pati (Kamaluddin & Handayani, 2018;Shafi'i et al, 2013;Sukasih & Widayanti, 2022). Pada penelitian ini hidrokoloid yang digunakan adalah CMC.…”
unclassified